Epidemiological and Spatial Distribution of COVID-19 Morbidity and Mortality in Nepal - Poudyal, Amod Kumar; Shakya, Karuna Laxmi; Sapkota, Vishnu Prasad; Paudel, Rajan; Myia, Salau Din; Pradhan, Pranil Man Singh; Upadhyaya, Dipak Prasad; Joshi, Naresh Prasad; Shrestha, Shital (Journal of Nepal Health Research Council, 2024)
Background: The Coronavirus (SARS-CoV-2) infection termed as COVID-19 was first detected in Wuhan, Hubei Province of China, in December 2019 and has been declared as a pandemic by the World Health Organization on January 30, 2020. The study aims to understand the time, place and person distribution of covid-19 morbidity, mortality of COVID-19 in Nepal.Methods: The analysis produces the descriptive epidemiological features of COVID-19 pandemic in Nepal. The data was analysed to produce disaggregated case rate and case fatality rate across various time, place and personal characteristics aggregated at national and subnational levelResults: The study found that the observed case rate was significantly higher among males compared to females. Similarly, case rate was the highest among males of 31-40 years and females of 51- 60 years. Case fatality rate increased with age group. Above the age of 41-50 years, case fatality rate was higher among males compared to females. We observed that case fatality rate was disproportionately concentrated among the poor districts in terms of GDPConclusions: The observed case rate is significantly higher among males compared to females, however case fatality rate increased with age group. Case rate was found the highest in the Bagmati province followed by the Gandaki Province. However, case fatality rate was found the highest in hilly and mountain districts of Province 1, Gandaki and Karnali. Case fatality rate was disproportionately concentrated among the poor districts in terms of GDP. Keywords: COVID19; morbidity; mortality; Nepal.